Evaluation of Americium Solubility in Synthesized Groundwater: Geochemical Modeling and Experimental Study at Over-Saturation Conditions - Kim, Hee-Kyung; Cho, Hye-Ryun (Journal of nuclear fuel cycle and waste technology (Online), 2022)
The solubility and species distribution of radionuclides in groundwater are essential data for the safety assessment of deep underground spent nuclear fuel (SNF) disposal systems. Americium is a major radionuclide responsible for the long-term radiotoxicity of SNF. In this study, the solubility of americium compounds was evaluated in synthetic groundwater (Syn- DB3), simulating groundwater from the DB3 site of the KAERI Underground Research Tunnel. Geochemical modeling was performed using the ThermoChimie_11a thermochemical database. Concentration of dissolved Am(III) in Syn-DB3 in the pH range of 6.4–10.5 was experimentally measured under over-saturation conditions by liquid scintillation counting over 70 d. The absorption spectra recorded for the same period suggest that Am(III) colloidal particles formed initially followed by rapid precipitation within 2 d. In the pH range of 7.5–10.5, the concentration of dissolved Am(III) converged to approximately 2×10−7 M over 70 d, which is comparable to that of the amorphous AmCO3OH(am) according to the modeling results. As the samples were aged for 70 d, a slow equilibrium process occurred between the solid and solution phases. There was no indication of transformation of the amorphous phase into the crystalline phase during the observation period.